Recurrence in Uterine Tumors with Ovarian Sex-Cord Tumor Resemblance: A Case Report and Systematic Review - Günsu KIMYON CÖMERT; Çiğdem KILIÇ; Deniz ÇAVUŞOĞLU; Osman TÜRKMEN; Alper KARALOK; Taner TURAN; Derman BAŞARAN; Nurettin BORAN (Federation of Turkish Pathology Societies, 2018)
Objective: The aim of this study was to evaluate the prognostic factors of recurrence in uterine tumors resembling ovarian sex-cord tumors (UTROSCT) and to determine clinical-pathological characteristics, treatment options and outcome. Material and Method: An electronic literature search was conducted from 1976 to 2018. After the comprehensive evaluation and conjunction with our case, the study included 79 cases. Results: The median age at initial diagnosis was 49 years (range; 16-86 years). The age was under 40 years in 21 (26.6%) patients. Whereas 68 patients underwent at least hysterectomy, 9 patients had organ sparing surgery. There was necrosis in 4 (5.1%) patients, atypia in 16 (20.3%) patients, and infiltrative tumor border in 34 (43%) patients. At least one mitosis per 10 high power fields was determined in 36 (45.5%) patients. The tumor involved at least part of the myometrium in 54 (68.3%) patients. Median follow-up time was 30 months (range; 3-296 months). Recurrence was determined in 5 (6.3%) patients. The disease free survival (DFS) was significantly related only to surgery type. None of the pathologic features were associated with DFS. The 5-year DFS was 86% and 96% in patients who underwent organ sparing surgery or not, respectively (p=0.038). Conclusion: The accurate pathologic diagnosis of UTROSCT has great value in shaping surgical management and management during the follow-up period. Organ sparing surgery was related to poor DFS. Although recurrence is rare, it should be kept in mind for patients with UTROSCT.